Prenatal diagnosis of giant cardiac rhabdomyoma in tuberous sclerosis complex: a new therapeutic option with everolimus. (May 2015) - Mlczoch, E.; Hanslik, A.; Luckner, D.; Kitzmüller, E.; Prayer, D.; Michel‐Behnke, I.
ABSTRACT: Tuberous sclerosis complex (TSC) is a genetic disorder characterized by abnormal cell proliferation and tumor growth in a number of organ systems, primarily the brain, kidneys, eyes and heart. Clinical symptoms vary according to the location of the tumor. The most common disorders are seizures, neurodevelopmental disorders, renal failure and arrhythmias. TSC was found to be influenced by inhibitors of the protein kinase mammalian target of rapamycin (mTOR), which regulates abnormal cellular proliferation. mTOR inhibitors have been studied effectively in patients with subependymal giant‐cell astrocytomas and renal angiolipomas in the context of TSC. We describe a prenatally diagnosed case of giant rhabdomyoma, due to right ventricular outflow tract obstruction, which presented as a duct‐dependent lesion. Postnatal treatment with the mTOR inhibitor everolimus initiated significant regression of the cardiac tumor. This finding suggests that mTOR inhibitor therapy is an option for giant rhabdomyomas that develop in the neonatal period. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.